2010
DOI: 10.1016/j.phrs.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Enabling individualized therapy through nanotechnology

Abstract: Individualized medicine is the healthcare strategy that rebukes the idiomatic dogma of ‘losing sight of the forest for the trees’. We are entering a new era of healthcare where it is no longer acceptable to develop and market a drug that is effective for only 80% of the patient population. The emergence of “-omic” technologies (e.g. genomics, transcriptomics, proteomics, metabolomics) and advances in systems biology are magnifying the deficiencies of standardized therapy, which often provide little treatment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(94 citation statements)
references
References 449 publications
(448 reference statements)
0
93
0
1
Order By: Relevance
“…Many researchers have been reported that, implantable drug delivery systems can be divided into two classes (Figure 3; Grayson et al, 2003;Staples et al, 2006;Nisar et al, 2008;Receveur et al, 2007;Daniel et al, 2009;Sakamoto et al, 2010;Stevenson et al, 2012) (a) Active device or solid-state silicon microchip -controlled drug releasing system after implantation using mechanical, electrical, magnetic, laser or other means. (b) Passive device or resorbable polymeric microchip -predetermined drug releasing system by the materials, fabrication methods or drug formulation and cannot be controlled after implantation.…”
Section: Theory Of Operationmentioning
confidence: 99%
“…Many researchers have been reported that, implantable drug delivery systems can be divided into two classes (Figure 3; Grayson et al, 2003;Staples et al, 2006;Nisar et al, 2008;Receveur et al, 2007;Daniel et al, 2009;Sakamoto et al, 2010;Stevenson et al, 2012) (a) Active device or solid-state silicon microchip -controlled drug releasing system after implantation using mechanical, electrical, magnetic, laser or other means. (b) Passive device or resorbable polymeric microchip -predetermined drug releasing system by the materials, fabrication methods or drug formulation and cannot be controlled after implantation.…”
Section: Theory Of Operationmentioning
confidence: 99%
“…Finally, it is important to note that first examples with polymer conjugates show that the panacea of enabling specific and individualised therapy through nanomedicine is becoming a feasible approach and polypeptidic carriers are major players in this role [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Среди протеомных методов, перспективных для персонализированной медицины, следует отметить белковые биочипы, на которых иммобилизованы связы-вающие белки -антигены, антитела, ферменты [33], масс-спектрометрическую визуализацию тканей чело-века, или имиджинг [35,39], и некоторые др. [40].…”
Section: от традиционной клинической диагностики к персонализированноunclassified